Enabling change a five year library information technology development plan for strengthening the services of Technological Institute of the Philippines (TIP) - Balatay, Lani C.; Faderon, Rosalie B.; Carcellar, Marie Desiree R.; Tinao, Maria Maura S.; Technological Institute of the Philippines (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2007)
Libraries are undergoing changes because of information and communication technologies. Library processes that were once done manually are now being computerized.
The Technological Institute of the Philippines must adapt to the changing technology in order not to be left behind. It is towards this end that this research was carried out. The methodology for this study was a survey on the identification of information technology needs of the TIP library users to enable change in providing library services and access to information and for the formation of an information technology development plan for strengthening its services.
Findings showed that majority of the hardware and software enumerated in the questionnaire were necessary in the respondents' research almost all of the time (100). Majority of the respondents were skilled (full use of basic features but not advanced features) in using the hardware and software enumerated in the questionnaire and they used them in their research work, professional/personal development about once a month, while those who did not use the hardware and software said that they did not use them because these were not appropriate in their research work, personal or professional development.
All the hardware and software were definitely important (100) in the research of the respondents. They also needed training in using them. Furthermore, staff competency on the hardware and software was also definitely important (100) to the respondents.
Respondents evaluated the library facilities as excellent and very satisfactory on library resources, library services, library rules and regulations and library staff. Respondents were aware of the library rules and regulations and they were very satisfied with the library hours.
TIP libraries have an adequate number of computers allocated for the library users but need additional units for the administrative works of the librarian and library staff, especially in TIP Quezon City library. They need printers, as well. Moreover, TIP libraries had no technologies integrated in the technical service processes and library services such as digital camera, scanner, multimedia computer, videodisc player and OPAC with complete modules.
Library users in general were very satisfied (75) with the library services based on the customer satisfaction evaluation survey. The researcher concluded that the hardware and software (systems software, applications software and programming languages) were needed by the library users and that these should be provided in order to meet their needs. The physical facilities and resources of the library were rated as very satisfactory (75) while the services, facilities and resources of the library met the needs of the library users. They had rated the said facilities, services and resources as excellent (100) and very satisfactory (75).
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library planning; Libraries -- User satisfaction -- Philippines -- Manila; Libraries -- User satisfaction -- Philippines -- Quezon City